PENGARUH RISIKO KEUANGAN TERHADAPA KINERJA KEUANGAN PADA PERBANKAN INDONESIA - Teguh Iman Laan; Wehelmina M. Ndoen; Hironnymus Jati (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The reserarch aims to determine and test the effect of financial risk on the financial performace of banks (the case study on banks listed on te Indonesian stock exchange). The indicator usud in this reserach is the Return on Assets (ROA) for Financial Performance, Operational Efficiency Ratio (BOPO) for Operational Risk, Capital Adequacy Ratio (CAR) for Capital Risk, Loan to Deposit Ratio (LDR) for Liquidity Risk, dan Non Performing Loan (NPL) for Credit Risk. This study took a sample of banking compies listed in Indonesian Stock exchange from 2016-2020 and the sampling technique using puposive sampling technique. The sample obtained is 6 sample company. The analysis used in this study is analysis panel data regression. The parcial test show that operation risk has negative but not significant effect on financial performance, capital risk has a postive and significant effect on financial performance, liquidity risk has negative but not significant effect on financial performance and credit risk has negative and significant effect on financial performance. Meanwhile, the simultaneous show that the financial risk has significant effect on financial performance. Keywords : Financial Performance, Fianancial Risk, Operation Risk, Capital Risk, Liquidity Risk, And Credit Risk